Calcium signal dynamics in T lymphocytes: Comparing in vivo and in vitro measurements. (October 2019) - Friedmann, Kim S.; Bozem, Monika; Hoth, Markus
Graphical abstract: Abstract: Amplitude and kinetics of intracellular Ca 2+ signals ([Ca 2+ ]int ) determine many immune cell functions. To mimic in vivo changes of [Ca 2+ ]int in human immune cells, two approaches may be best suited: 1) Analyze primary human immune cells taken from blood under conditions resembling best physiological or pathophysiological conditions. 2.) Analyze the immune system in vivo or ex vivo in explanted tissue from small vertebrate animals, such as mice. With the help of genetically encoded Ca 2+ indicators and intravital microscopy, [Ca 2+ ]int have been investigated in murine T lymphocytes (T cells) in vivo during the last five years and in explanted lymph node (LN) during the last 10 years. There are several important reasons to compare [Ca 2+ ]int measured in primary murine T lymphocytes in vivo and in vitro with [Ca 2+ ]int measured in primary human T lymphocytes in vitro . First, how do human and murine data compare? Second, how do in vivo and in vitro data compare? Third, can in vitro data predict in vivo data? The last point is particularly important considering the many technical challenges that limit in vivo measurements and to reduce the number of animals sacrificed. This review summarizes and compares the results of the available publications on in vivo and in vitro [Ca 2+ ]int measurements in T lymphocytes stimulated focally by antigen-presenting cells (APC) after forming an immunological synapse.